E-Commerce Implementation of SMEs in Indonesia - As'ad, Ihwana (2008)
During the economic crisis, Indonesia learned that small and medium-scale businesses, known as "Usaha Kecil dan Menengah" have helped the economy to survive, and have improved the country's economy, through the e-commerce. "Usaha Kecil dan Menengah" (UKM) is also known as Small and Medium enterprises (SMEs). Since then the Indonesian government has recognized the importance of having modern SMEs as an important element in creating a sophisticated economy. especially through their role in developing inter-industry linkages, or as supporting industries producing components and parts for large enterprises either via market mechanisms or subcontracting systems or other forms of production linkages. Currently there are about 48.9 million SMEs in Indonesia, in which, out of this amount less than one percent (1%) have started conducting business electronically. However, the Indonesia government has not been able to find information on current business situation. This research intends to explore e-commerce implementation by SMEs in Indonesia. The research also investigates the current usage and problem in Indonesia's e-commerce implementation. The study has been successful in achieving all objectives. Implementation of e-commerce in SMEs has grown in the last 2 years. There are some problems in the execution of e-commerce of SMEs in Indonesia. These can be categorized as follows: internet connectivity, stock clarification; bank administration; and goods distribution to buyers. This study found that there are some catalysts that encourage implementation of e-commerce. Among these are increase in sales revenue, low expenses in development and maintenance of a website, and increase in numbers of customers.